Legitimacy of Sub-Minimum Sentencing in Narcotics Cases: An Analysis of Judicial Discretion from the Perspectives of Positive Law and Islamic Criminal Law - Ahmad Farhan Jumain; Ramadani (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
This article examines the legitimacy of sub-minimum sentencing in narcotics cases through a normative analysis of Indonesian Supreme Court Decision No. 4634 K/Pid.Sus/2023, which imposed a sentence below the statutory minimum prescribed under Article 112 of Law No. 35 of 2009. Employing a doctrinal legal method with comparative analysis and systematic literature review, the study evaluates judicial reasoning across the District Court, High Court, and Supreme Court levels. The findings indicate that, from the perspective of positive law, the decision potentially undermines the principles of legality and legal certainty due to the absence of a clear normative basis for departing from the mandatory minimum, thereby increasing the risk of sentencing disparity. Conversely, from the perspective of Islamic criminal law, the decision attains normative legitimacy within the framework of taʿzīr and maqāṣid al-sharīʿah, particularly the protection of intellect (ḥifẓ al-ʿaql), which prioritizes proportionality and rehabilitative objectives for drug users. Nevertheless, this legitimacy is procedurally weakened by the lack of objective supporting evidence, notably a medical or clinical assessment as a prerequisite for judicial ijtihād. This article proposes an integrative model in the form of a minimum evidentiary checklist and mandatory clinical assessment to ensure that judicial discretion remains legally accountable while coherently reconciling substantive justice, legal certainty, and Islamic normative principles.